The role of optical coherence tomography angiography to detect early microvascular changes in diabetic retinopathy: a systematic review - Palma, Filipa (2021)
Purpose To evaluate quantitative parafoveal microvascular changes using Optical Coherence Tomography Angiography (OCTA) by comparing the area of the foveal avascular zone (FAZ) and vessel density (VD) between non-diabetic controls and patients with different levels of Diabetic Retinopathy (DR). Methods A systematic review was performed according to the recommendations of the "Cochrane Handbook for Systematic Reviews of Interventions" and reported according to the Preferred Reporting Items for Systematic Reviews and Meta-Analysis (PRISMA) guidelines. Three electronic databases including PubMed, Web of Science, and Cochrane Library were systematically retrieved by using key terms with Boolean operators. The data extracted from each study included: first author, year of publication, study design, sample size, and participant characteristics (mean age, type of diabetes mellitus, and mean duration of diabetic disease). Outcome variables included: VD and area of FAZ, in superficial and deep capillary plexuses of parafovea. Results 355 articles were identified from our search of databases and 10 studies were included in this systematic review. Patients with diabetes with or without clinical signs of DR have a significantly enlarged area of FAZ and decreased parafoveal VD compared to healthy controls, as well as an association between these microvascular changes and worsening DR. Conclusion OCTA can provide valuable information about early and subtle microvascular changes of parafoveal capillary plexuses in patients with diabetes and can identify preclinical DR before the manifestation of clinically apparent retinopathy. The non-invasive nature of OCTA allows routine imaging of the retinal vasculature, so this approach may be a promising tool for screening programs of DR.